First intermissions : twenty-one great operas explored, explained, and brought to life from the Met - Lee, M. Owen, 1930-2019 (Oxford University Press, 1996)
As many as eight to ten million music lovers in the United States, Canada, and Europe have heard the moving words of Father Owen Lee during the first intermissions of the Saturday afternoon operas broadcast live from the Metropolitan Opera in New York. His illuminating, intensely personal, immediately accessible half hours on the air have brought grateful letters by the thousand from both first-time listeners and veterans of fifty years of Met broadcast listening, from professors of music, art, literature, psychology, and science as well as from the general public.